Décrire la ville, écrire le patrimoine - Jean-Claude David (Revue des Mondes Musulmans et de la Méditerranée)
In the context of the Middle East, at least since the eleventh century, “city narratives”, a common literary genre, have been used as a way of substantiating individual and collective identity links with the living and changing urban entity, in this way giving the city a form of global identity beyond what might otherwise amount to a mere collection of isolated monuments or spatial constructs. Thus, with an urban heritage that is both an affirmation and expression of a periodically renewed lifestyle and an integral part of a shared local identity, Arab historians and geographers search for traces of the past, seeking to understand the appearance, persistence and disappearance of this past through narrative. The co-existence in contemporary Aleppo of various conceptions of “heritage” could explain the population’s apparent indifference to the destruction of historical monuments qualified as official heritage. On the other hand, the populations of the historical and unincorporated neighbourhoods suffering in the violence of the civil war are precisely those heirs of traditional society for whom the memory of lifestyles and routine practices form a basis for heritage and confirm the written narratives of the ancient cities?